High serum neurofilament associates with diffuse white matter damage in MS - Saraste Maija; Bezukladova Svetlana; Matilainen Markus; Tuisku Jouni; Rissanen Eero; Sucksdorff Marcus; Laaksonen Sini; Vuorimaa Anna; Kuhle Jens; Leppert David; Airas Laura (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2022)
Objective To evaluate to which extent serum neurofilament light chain (NfL) increase is related to diffusion tensor imaging-MRI measurable diffuse normal-appearing white matter (NAWM) damage in MS.
Methods Seventy-nine patients with MS and 10 healthy controls underwent MRI including diffusion tensor sequences and serum NfL determination by single molecule array (Simoa). Fractional anisotropy and mean, axial, and radial diffusivities were calculated within the whole and segmented (frontal, parietal, temporal, occipital, cingulate, and deep) NAWM. Spearman correlations and multiple regression models were used to assess the associations between diffusion tensor imaging, volumetric MRI data, and NfL.
Results Elevated NfL correlated with decreased fractional anisotropy and increased mean, axial, and radial diffusivities in the entire and segmented NAWM (for entire NAWM ρ = −0.49, p = 0.005; ρ = 0.49, p = 0.005; ρ = 0.43, p = 0.018; and ρ = 0.48, p = 0.006, respectively). A multiple regression model examining the effect of diffusion tensor indices on NfL showed significant associations when adjusted for sex, age, disease type, the expanded disability status scale, treatment, and presence of relapses. In the same model, T2 lesion volume was similarly associated with NfL.
​​​​​​​Conclusions Our findings suggest that elevated serum NfL in MS results from neuroaxonal damage both within the NAWM and focal T2 lesions. This pathologic heterogeneity ought to be taken into account when interpreting NfL findings at the individual patient level.